Opportunity of Leprosy Information Systems as An Effort to Eliminate Leprosy in Papua: Systematic Review - Bahari, Bahari; Sutantri, Sutantri; Huriah, Titih (Universitas Aisyah Pringsewu, 2022)
Leprosy is a significant health problem in certain countries, including Indonesia. Indonesia has six provinces that have been unable to eliminate leprosy, including Papua. Most leprosy elimination constraints are caused by drinking compliance, socio-cultural factors, health services, and the development of information systems to eliminate leprosy. This study discussed the leprosy information system in the situation in Papua. The applied approach was a systematic review. The researchers reviewed the articles from ProQuest, Ebscohost Medline, Emerald, Clinical key, Science Direct, and Sage Journal databases from 2018-2022. The researchers also applied keywords to filter sources. The author found 329 articles however only six papers met the requirements for analysis. The review found that the information system was an integrated application with reminders, artificial intelligence, epidemiological modeling, and geographic applications. These articles were useful to differentiate some matters, such as detections, reminders, geospatial data, epidemiological modeling, vaccines, and analysis of application reliability with artificial intelligence assistance. Abstrak: Kusta merupakan masalah kesehatan utama di negara-negara tertentu termasuk Indonesia. Indonesia sendiri terdapat enam provinsi yang belum dapat mengeliminasi kusta termasuk Papua. Kendala eliminasi kusta mayoritas disebabkan karena kepatuhan minum, factor sosial-budaya, dan layanan kesehatan. Mengikuti perkembangan sistem informasi yang akhir-akhir ini berkembang pesat dapat dimanfaatkan dalam upaya eliminasi kusta. Untuk itu penelitian ini akan membahas tentang pemanfaatan sistem informasi kusta yang sesuai dengan keadaan Papua. Pendekatan yang digunakan dalam tulisan ini ialah sistematis review pada artikel jurnal memanfaatkan database ProQuest, Ebscohost medline, Emerald, Clinicalkey, Science Direct dan Sage Journal dalam rentang 2018-2022 dan menggunakan kata kunci untuk menyaring sumber. Penulis menemukan sebanyak artikel 329 artikel yang kemudian terdapat 6 artikel yang memenuhi syarat untuk dilakukan analisa. Review menemukan bahwa system informasi yang digunakan yakni aplikasi yang di integrasikan dengan pengingat, artificial intelligen, pemodelan epidemiologi serta aplikasi geografis. Artikel-artikel tersebut mempunyai fungsi dan tujuan yang cenderung berbeda satu sama lain baik pada deteksi sini, reminder, data geospasial, pemodelan epidemiologi, vaksin serta analisa kehandalan aplikasi dengan bantuan kecerdasan buatan.